The guidance coordinator a descriptive profile - Ovejera, Maria I. 1932-
This study was inspired by the need for a comprehensive and organized body of information about the guidance counselors in the Bureau of Public Schools, so that proper evaluations, revisions and recommendations may be made prior to their recruitment. This research was therefore conducted to establish a decriptive profile of the guidance coordinators in the Division of Tarlac.